Assessment of renal response with urinary exosomes in patients with AL amyloidosis: A proof of concept. Issue 6 (4th May 2017) - Ramirez‐Alvarado, Marina; Barnidge, David R.; Murray, David L.; Dispenzieri, Angela; Marin‐Argany, Marta; Dick, Christopher J.; Cooper, Shawna A.; Nasr, Samih H; Ward, Christopher J.; Dasari, Surendra; Jiménez‐Zepeda, Víctor H.; Leung, Nelson
Abstract: Immunoglobulin light chain (AL) amyloidosis is a fatal complication of B‐cell proliferation secondary to deposition of amyloid fibrils in various organs. Urinary exosomes (UEX) are the smallest of the microvesicles excreted in the urine. Previously, we found UEX of patients with AL amyloidosis contained immunoglobulin light chain (LC) oligomers that patients with multiple myeloma did not have. To further explore the role of the LC oligomers, UEX was isolated from an AL amyloidosis patient with progressive renal disease despite achieving a complete response. LC oligomers were identified. Mass spectrometry (MS) of the UEX and serum identified two monoclonal lambda LCs. Proteomics of the trypsin digested amyloid fragments in the kidney by laser microdissection and MS analysis identified a λ6 LC. The cDNA from plasma cell clone was from the IGLV‐ 6‐57 family and it matched the amino acid sequences of the amyloid peptides. The predicted mass of the peptide product of the cDNA matched the mass of one of the two LCs identified in the UEX and serum. UEX combined with MS were able to identify 2 monoclonal lambda LCs that current clinical methods could not. It also identified the amyloidogenic LC which holds potential for response assessment in the future.